Scientific Rationale for The Use of Low-Intensity Sprinkling Systems in Mountain Irrigated Agriculture in Azerbaijan - Aliyev, RAE. Z.H.; Aliyev, B.H. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2019)
The results of the study revealed that the mismatch intensity rain rate of water absorption into the soil formation of a surface relief and soil erosion, uneven and shallow soaking imperfection open irrigation system at a superficial irrigation, the need for different irrigation methods in the growing and not growing periods, low coefficient land utilization, high cost of irrigation and other features are, to a certain extent in conflict with the requirements of watering cultivated with techniques for / of crops in an area at the deep groundwater